Педагогічні умови формування комунікативної культури майбутніх фахівців інженерно-технічних спеціальностей - Галацин, Катерина; Halatsyn, K. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розкривається сутність поняття комунікативної культури особистості, її структура та особливості формування у майбутніх фахівців інженерно-технічного спрямування. Визначаються та аналізуються провідні педагогічні умови успішного формування комунікативної культури у майбутніх інженерів; окреслюються основні напрями вирішення проблеми формування комунікативної культури майбутнього фахівця як важливої складової його професійної майстерності. In article the essence of a concept of communicative culture of the personality, its structure and forming features of future specialists on the technical direction reveals. The leading pedagogical peculiarities of successful communicative culture forming of future engineers are determined and analyzed: focus and systematicness of the teaching and educational process organization at higher technical educational institution; updating of teaching content and educational work taking into account the communicative potential of future engineers; implementation of interactive forms and methods of the communicative culture forming of the future engineers; management of the communicative culture process forming of the students by the teaching staff.
Pedagogical peculiarities of the communicative culture formation of the future engineers.
Keywords: комунікативна культура; communicative culture; формування комунікативної культури майбутнього фахівця; специфіка формування комунікативної культури у майбутніх інженерів; педагогічні умови; formation of communicative culture of the future expert; specifics of formation the communicative culture of future engineers; pedagogical peculiarities